THE ENERGY POLICY ACT AND ITS CATEGORICAL EXCLUSIONS: WHAT HAPPENED TO THE EXTRAORDINARY CIRCUMSTANCE EXCEPTION? (Utah Environmental Law Review; Vol 28 No 1 (2008), 2009)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} The National Environmental Policy Act and the Federal Land Policy and Management Act are evidence that Congress recognized the importance of public land protection in conjunction with development of our natural resources. However, as this country continues to grow, demand for natural resources is increasing. Specifically, oil and gas development has dramatically increased, causing unavoidable impacts to air, water, and wildlife. The competing values of land protection and natural resource extraction have come to a head and the oil Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 st1\:*{behavior:url(#ieooui) } /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} and gas industry is winning the battle in Congress. Critics of NEPA are accusing it of being "a stick in the spokes of the wheels of progress" and contrary to natural resource development goals. Evidence of this new trend toward an emphasis on development can be found within the language of the National Energy Policy Act of 2005 (EPAct). Specifically, § 390 allows land management agencies to apply categorical exclusions (CXs) on projects, eliminating NEPA review without a caveat for extraordinary circumstances. Agencies commonly use CXs for minor actions that will not significantly affect the environment.   However, federal regulations that control the use of CXs, contain a caveat for extraordinary circumstances that bars the normal application of a CX when there are sensitive areas at issue such as a crucial habitat area or migration corridor. The CXs prescribed by § 390 of the EPAct do not have a similar safety valve to ensure sensitive areas and resources are not overlooked when a CX is applied.